Do Skepticism, Independence, and Competence Matter? Evidence on Factors Influencing Auditors’ Fraud Detection Ability - Asmara, Rina Yuliastuty (Research Horizon, 2025)
This study addresses a critical gap by exploring how individual auditor attributes affect fraud detection performance in the public sector context. This study aims to examine the influence of professional skepticism, independence, and professional competence on internal auditors’ ability to detect fraud within ministries and governmental institutions in Indonesia. A quantitative causal research design was employed, using a stratified random sampling technique to collect data from 96 internal auditors across various Indonesian ministries and agencies. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess first- and second-order constructs. The results show that all three independent variables significantly influence fraud detection ability. Among them, independence has the strongest effect, followed by professional competence and professional skepticism. These findings underscore the importance of maintaining auditor autonomy and enhancing technical capabilities to improve fraud detection in the public sector. The study suggests that government institutions should prioritize training programs that strengthen auditors’ independence and professional competence. Internal audit policies must also reinforce structural independence to ensure objective fraud detection efforts.